Biological Wastewater Treatment: Dynamic Global Sensitivity Analysis and Parameter Estimation in a System of Waste Stabilization Ponds - Iturmendi, Facundo (2012)
Fil: Iturmendi, Facundo. Universidad Nacional del Sur. Planta Piloto de Ingeniería Química (PLAPIQUI). CONICET; Argentina.